SISTEM PENGELOLAAN LIMBAH FESES AYAM PEDAGING DI PETERNAKAN PT JANUPUTRA SEJAHTERA FARM - , ADITYA SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of practical work at third cage of PT Januputra Sejahtera Farm, Bokong, Seyegan, Sleman, Yogyakarta was to understand about the management of poultry faeces waste processing. The method used was interview and practical work from March 10 to 15th 2014. Waste product management system include: fecal treatment prior new DOC arrive, fecal management during growth period, fecal and envirroment relationship, minimum distance between farm to the village and water resources and geographical contur the farm-higher or lower compare to the surronding area. Waste product management system have been implemented PT Januputra Sejahtera Farm thought still very simple since the fecal was keep in place under the the eage until harvest time. To develop the waste product management system it is recommended to clean the fecal twice a week. To reduce the fecal smell, it can treated by zeolith, fermenter or calcic.